Kajian Komoditas Unggulan Perikanan Tangkap Kabupaten Situbondo Berdasarkan Data Penangkapan Ikan - Anita Diah Pahlewi; Creani Handayani (Jurnal Manajemen Pesisir dan Laut, 2023)
The capture fisheries sector is one of the sectors that play an important role in national economic development, provision of protein food, foreign exchange capture, and employment opportunities. The capture fisheries sector makes a major contribution as a leading commodity in Situbondo Regency with the longest coastline in East Java. Leading commodities are needed as an effort to determine development in the fisheries sector and can improve the regional economy. The purpose of this study is to discuss the calculation of superior fisheries commodities in 4 Districts of Situbondo Regency that have the greatest catch potential using the Location Quotient (LQ) method. LQ measures the specialization of economic activity through a comparative approach to get an overview in determining the leading sector as the leading sector of industrial economic activity. Based on the Location Quotient (LQ) method, the leading capture fisheries commodities in Besuki District are Layang, Teri, and Tongkol; Panarukan District, namely Kakap, Pari, Teri, Rajungan, Crab, shrimp, and other fish; Jangkar District, namely Petek, Beloso, Bambang, Kakap, Kurisi, Cucut, Bawal, Selar, Belanak, Teri, Crab, Layur fish; Banyuputih District, namely Petek, Beloso, Belanak, Teri, and Layur fish.